Rating agencies and sovereign credit risk assessment - Nicolas Véron; Guntram B. Wolff (Bruegel, 2011)
Credit rating agencies (CRAs) have not consistently met the expectations placed on them by investors and policymakers. It is difficult, however, to improve the quality of ratings through regulatory initiatives. In the short term, changes to the CRAs' regulatory environment, in a context of high market uncertainty, may add to market stress. The role of credit ratings in regulation should be reduced but eliminating it entirely would have significant downsides, at least in the short term. The transfer of ratings responsibility to public authorities, including the European Central Bank, is unlikely to be a good alternative because of inherent conflicts of interest. The notion of risk-free sovereign bonds is challenged by the crisis, but the most straightforward way to address this challenge in the euro-area context would be the establishment of a euro-area-wide sovereign bond instrument. This Policy Contribution was prepared as a briefing paper for the European Parliament's Economic and Monetary Affairs Committee's Monetary Dialogue.
Keywords: 330; Ratingagentur; Länderrisiko; Öffentliche Anleihe; Eurozone; EU-Staaten